Analisa Data Profil Pelanggan Menggunakan Algoritma FP-Growth - Suryani, Vivi; Defit, Sarjon; Yunus, Yuhandri (Jurnal Informasi dan Teknologi, 2020)
The number of bouquet orders is quite varied sometimes increased and decreased. The number of hikes certainly carries the goodness but the amount of decline certainly has an impact for Wawa Florist because it can not fulfill the number of bouquet order. The purpose of this research is to know how Data Mining techniques with Fp-Growth algorithm methods and designing the grouping of customer data of Wawa Florist with the FP-Growth algorithm method to obtain better and more effective analysis results. The result of the order data of the wreaths in Wawa Florish can be obtained which area information most booked wreaths, the most ordered bouquet of flowers are: D02 (Lubuk Buaya), D04 (Lubuk Minturun), D01 (Pariaman) and D03 (Lubuk Alung ). These results are obtained based on the appearance of the itemset of the bouquet booking data. Meet minimum confidence 60%.